Messiaen Perspectives - Dingle, Christopher; Fallon, Robert (Surrey Ashgate Publishing, 2013)
Focusing on Messiaen's relation to history - both his own and the history he engendered - the Messiaen Perspectives volumes dispel the entrenched sentiment that Messiaen was, as the New Grove Dictionary says, 'a musician apart'. Messiaen Perspectives 1: Sources and Influences examines the genesis, sources, and cultural pressures that shaped Messiaen's music. By contrast, Messiaen Perspectives 2: Techniques, Influence and Reception analyses the repercussions of Messiaen's music - its techniques, influence, and reception - on later musical history. Together, these volumes promise to elucidate how powerfully Messiaen was connected to his time and place, thus reversing the predominant view of his role in history. Messiaen Perspectives 1: Sources and Influences presents key primary sources for the first time, including sketch materials for Visions de l'amen, La Transfiguration and La fauvette des jardins, the first detailed information regarding the music and circumstances of the recently rediscovered Portique pour une fille de France. It also introduces key documents relating to the Vingt regards, Timbres-durées and Méditations sur le mystère de la Saint Trinité, and outlines radical interpretative elements in Harawi, drawing upon recorded rehearsals with the composer. The volume also presents invaluable new insights into Messiaen's sources of inspiration, placing the composer within a broader historical and cultural framework than has hitherto been attempted. These range from specific cases, such as Mozart and Messiaen's treatment of found material, to more general contexts, such as the Romantic piano tradition. For the final essay, the editors have deliberately invited a non-specialist, Hugh MacDonald, to provide his perspective upon Messiaen's cultural background and position. As a centrepiece, the book includes an examination of the career of one of the greatest influences upon Messiaen, Yvonne Loriod.« Minder
Keywords: Messiaen, Olivier -- 1908-1992; 20th Century (1901-2000); Composer; Influence; Reception; France